NIETZSCHE AND THE ETHICS ON PLAY: PHILOSOPHICAL NOTES (Fiep Bulletin - online, 2015)
The present paper has the purpose to set up a theoretical reflection concerning the ethical dimensions of play, adopting as conceptual basis presuppositions of the philosophy of Friedrich Nietzsche.
Keywords: Play; Philosophy; Ethics; Nietzsche.